1992
DOI: 10.1111/j.1365-2362.1992.tb01940.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine before and after methionine loading with regard to age, gender, and menopausal status

Abstract: Homocysteine is a probably atherogenic amino acid, the fasting and post-methionine load serum concentrations of which have been reported to be much lower in premenopausal women than in men and postmenopausal women. This difference has been proposed to explain the reduced proneness of premenopausal women to vascular disease. We measured both free and total plasma homocysteine concentrations both fasting and post-methionine load, in 169 healthy subjects. Twelve subjects (7%) had distinctly abnormal plasma homocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
133
5
13

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(164 citation statements)
references
References 31 publications
13
133
5
13
Order By: Relevance
“…This difference may be due not only to the higher dose used (30 mg day-') but also to the abnormal baseline tHcy levels observed in most breast British Journal of Cancer (1998) 77(12), [2264][2265][2266] cancer patients (mean 12.4 gmol 1-') in comparison with normal women (8-9 ,tmol 1-') (Andersson et al, 1992;Nyg'ard et al, 1995). As the high tHcy levels found in breast cancer women might also reflect the activity of tumour cells, the possibility that the inhibitory effect induced by tamoxifen on tHcy was secondary to its antitumoral activity cannot be convincingly ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due not only to the higher dose used (30 mg day-') but also to the abnormal baseline tHcy levels observed in most breast British Journal of Cancer (1998) 77(12), [2264][2265][2266] cancer patients (mean 12.4 gmol 1-') in comparison with normal women (8-9 ,tmol 1-') (Andersson et al, 1992;Nyg'ard et al, 1995). As the high tHcy levels found in breast cancer women might also reflect the activity of tumour cells, the possibility that the inhibitory effect induced by tamoxifen on tHcy was secondary to its antitumoral activity cannot be convincingly ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study, Lolin et al (30) showed that the prevalence of hyperhomocysteinemia in Hong Kong Chinese patients with premature coronary artery disease wassimilar to that found in Caucasians. Although we did not follow a control group during this oneyear period, it is unlikely that their homocysteine concentrations would change (31). Wefailed to find a decline in serum folic acid in association with the elevation of homocysteine levels probably because the number of study subjects was relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…This might be partially explained by gender differences in the transsulfuration and remethylation of homocysteine, with a more efficient remethylation in women than in men (Fukagawa et al, 2000), who may have a more efficient transsulfuration (Silberberg et al, 1997). Hormone replacement therapy attenuates the increase in plasma homocysteine observed after menopause (Andersson et al, 1992;Mijatovic et al, 1998;van der Mooren et al, 1994). Black South Africans have lower homocysteine levels than white South Africans consuming the same diet, this resistance may be genetic in origin (Ubbink et al, 1995).…”
Section: Aging Gender Lifestyle Factors and Other Causesmentioning
confidence: 99%